Guest

If y = e- 4x (A cos 3x + B sin 3x) then a) (D2 – D – 12) y = 0 b) (D2 + 8D + 25 ) y = cos 3x + sin 3x c) (D2 + 8D + 25) y = 0 d) (D2 – 8D + 25 ) y = e- 4x

If y = e-
4x (A cos 3x + B sin 3x) then

a) (D2
– D – 12) y = 0 b) (D2
+ 8D + 25 ) y = cos 3x + sin 3x
c) (D2
+ 8D + 25) y = 0 d) (D2
– 8D + 25 ) y = e- 4x

Grade:

2 Answers

Saurabh Koranglekar
askIITians Faculty 10341 Points
2 years ago
Dear student

Please attach the image of the question

Regards
Vikas TU
14149 Points
2 years ago
Dear student 
Question is not clear 
Please attach an image, 
We will happy to  help you 
Good Luck
Cheers

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free